2020
DOI: 10.4238/gmr18617
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Genetic potential of fusarium wilt-resistant elite common bean lines assessed in multiple environments

Abstract: Fusarium wilt is a serious soil disease affecting common bean cultivation, especially crops under a central pivot irrigation system. Our objective was to identify bean lines that combine resistance to Fusarium wilt in the field with other desirable traits. Twenty-eight randomized block trials with three replicates were conducted in the rainy, winter, and dry seasons from 2009 to 2012 in the states of Goiás, Federal District, and Paraná. The trials were composed of six elite lines (one carioca and five black gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
5
9
0
Order By: Relevance
“…The estimates of the CV ranged from 20.8 to 29.0% (data not shown) for reaction to Fusarium wilt, considered acceptable due to the natural occurrence of the disease, the heterogeneous distribution of the fungus in the soil, and the low mean of the trait (Pereira et al, 2019a(Pereira et al, , 2020. The estimates of selective accuracy were considered very high, i.e., higher than 0.90 (data not shown), indicating good informativeness of the experiments for the selection of superior genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimates of the CV ranged from 20.8 to 29.0% (data not shown) for reaction to Fusarium wilt, considered acceptable due to the natural occurrence of the disease, the heterogeneous distribution of the fungus in the soil, and the low mean of the trait (Pereira et al, 2019a(Pereira et al, , 2020. The estimates of selective accuracy were considered very high, i.e., higher than 0.90 (data not shown), indicating good informativeness of the experiments for the selection of superior genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…All experiments were conducted in the experimental field of Embrapa Arroz e Feijão, located in the municipality of Santo Antônio de Goiás, in the state of Goiás,Brazil (16º30'17"S,49º16'53"W,at 819 m altitude). The area where the experiments were set up has a high natural infestation of the pathogen and has been used in other studies for the evaluation of the reaction to Fusarium wilt (Pereira et al, 2016(Pereira et al, , 2018(Pereira et al, , 2019a(Pereira et al, , 2020. In all experiments, water was supplied by a center pivot irrigation system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also suggested that MR and RVS should be combined to calculate disease severity rating (DSR) for a final accurate evaluation of cotton germplasm for FOV4 resistance (Zhang, Abdelraheem, Zhu, Wheeler, Dever, Elkins‐Arce et al., 2020). However, for almost all other crops with Fusarium wilt caused by different formae speciales of F. oxysporum , screening plants for resistance is exclusively performed on foliar symptoms with a few on SVD (e.g., Ahmad et al., 2020; Alvarez et al., 2005; Bani et al., 2012; Branham et al., 2019; Chitwood‐Brown et al., 2021; Dong et al., 2019; Leitão et al., 2020; Mahmoud & Abd El‐Fatah, 2020; Miyatake et al., 2016; Pereira et al., 2020; Siamak & Zheng, 2018). This has been the case for cotton with wilt caused by most FOV other than FOV4 (Hillock, 1992; Sanogo & Zhang, 2016; Wang & Roberts, 2006; Wang et al., 1999; Zhang et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variability has been reported for resistance to fusarium wilt (Pastor-Corrales & Abawi, 1987;Azevedo et al, 2015;Leitão et al, 2020;Pereira et al, 2011Pereira et al, , 2020, indicating the possibility of selection of resistant genotypes and of genetic gain for this trait.…”
Section: Introductionmentioning
confidence: 99%